Persuasive factors in determining customer satisfaction: a Malaysian e-commerce perspective / Muhammad Alihan Abdul Magfir Khan - Abdul Magfir Khan, Muhammad Alihan (2017)
E-Commerce and online shopping channels are continuing to grow along with internet users that are also expanding therefore the need to shop online also grows together. More and more Malaysian E-commerce or online shopping websites and platform are popping out in the internet which make the field even more competitive. New rival competitors with new selling strategies will eventually impact the online shopping company revenue due to products similarities that are being sold. Persuasive strategies have already been implemented by e-commerce companies in order to persuade and influence consumers to shop at their e-commerce platform. This study aims to understand and identify the persuasive principle used in online shopping which refer to Cialdinis principles and to determine which of the persuasive elements that can be the most influencing factors for customer e-satisfaction. Findings in the study shows that only three of the Cialdini persuasive principle (Liking, Social Consensus, Scarcity) does have a positive relation towards customer e-satisfaction. This research is based on quantitative research and the research model is based on an adapted model from Brent Coker which is an adaptation from Technology Acceptance Model (TAM). Data collection are based on distributed questionnaire with 120 respondents from UiTM post graduate students and ex UiTM students. The analysis such as reliability test, Pearson correlation test, variance inflation test and multi regression test that were conducted are describe in this report and was perform using Statistical Package for Social Science (SPSS).